The effect of giving cherry leaves boiled water (muntingia calabura l) on the healing of perineal wounds in postpartum mothers at the Dorara Primary Clinic, Sunggal Kanan Village, Deli Serdang Regency - Maulidanita, Riska; Br.Sembiring, Elya Rosa (Journal of Midwifery and Nursing, 2024)
Perineal tears often occur in normal labor, whose normal healing occurs 6-7 days postpartum. Improper handling of perineal wounds can cause infection, so it will increase the number of pain in the mother. The purpose of the study was to determine the effect of giving Kersen leaf boiled water (Muntingia calabura L) on the healing of perineal wounds in postpartum mothers.This study used quantitative data analysis and quasi-experimental research design with two groups, namely the control group and the intervention group. The study population was 10 postpartum mothers who gave birth starting from week 3 in July – week 2 in August at Pratama Dorara Clinic. The results showed that the intervention group given boiled water kersen leaves showed rapid wound healing as much as 5 (100.0%), and the control group showed normal wound healing as much as 4 (80%), and slow wound healing as much as 1 (20%). The results of the Wilcoxon Test obtained p value = 0.034 < 0.05 so that there is an effect of giving kersen leaf boiled water on perineal wound healing in postpartum mothers. The conclusion of the study is the effect of giving kersen leaf boiled water on the healing of perineal wounds in postpartum mothers at the Dorara Pratama Clinic, Sunggal Kanan Village, Deli Serdang Regency in 2023. It is recommended that puerperal mothers wash perineal wounds with water boiled cherry leaves to speed up the healing process of perineal wounds.